2019
DOI: 10.1093/beheco/arz199
|View full text |Cite
|
Sign up to set email alerts
|

Predators’ consumption of unpalatable prey does not vary as a function of bitter taste perception

Abstract: Many prey species contain defensive chemicals that are described as tasting bitter. Bitter taste perception is, therefore, assumed to be important when predators are learning about prey defenses. However, it is not known how individuals differ in their response to bitter taste, and how this influences their foraging decisions. We conducted taste perception assays in which wild-caught great tits (Parus major) were given water with increasing concentrations of bitter-tasting chloroquine diphosphate until they sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…Interestingly, we found that great tits consumed more unpalatable almonds when they were lighter, irrespective of which colour indicated unpalatability. This supports the idea that birds are more willing to consume chemically defended prey when they are in a poorer physiological condition (Barnett et al 2007(Barnett et al , 2012Skelhorn et al 2016;Hämäläinen et al 2020a). In contrast, we found the opposite effect in blue tits, with heavier individuals tending to attack more unpalatable food items than lighter birds.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, we found that great tits consumed more unpalatable almonds when they were lighter, irrespective of which colour indicated unpalatability. This supports the idea that birds are more willing to consume chemically defended prey when they are in a poorer physiological condition (Barnett et al 2007(Barnett et al , 2012Skelhorn et al 2016;Hämäläinen et al 2020a). In contrast, we found the opposite effect in blue tits, with heavier individuals tending to attack more unpalatable food items than lighter birds.…”
Section: Discussionsupporting
confidence: 80%
“…Medium ground finches fed most often on the bitter-flavoured pastry and wiped their beaks the least following its ingestion. This was surprising, given that bitter-tasting foods often elicit increased beak wiping in birds [25,54]. It is possible that our sample sizes were too small to detect preferences for human-food flavours, or that we did not add sufficient flavour to the pastry to be detectable.…”
Section: Discussionmentioning
confidence: 92%
“…latent), we predicted preferences would occur for such flavours across sites, regardless of the presence or absence of human foods. Potential taste preferences can be quantified as variation in feeding rate, or as variation in post-feeding beak wiping rate [25,[52][53][54]. Although beak wiping can clean the beak of debris [55], vigorous beak wiping commonly occurs after feeding on something unpalatable [25,54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even high evolutionary potential will only lead to evolutionary changes if the defense trait variation influences predation rates (Speed et al, 2012). In general, empirical data on the impact of variation in defenses and its signaling on predators is lacking, but there is evidence for variation among predators in traits including perceptual abilities, individual motivation and tolerance to chemical defenses (Halpin et al, 2017;Briolat et al, 2019;Hämäläinen et al, 2020). Predators may also respond not only to average defense levels, but to the variation in them (Skelhorn & Rowe, 2005;Barnett, Bateson & Rowe, 2014).…”
Section: Implications Of Evolutionary Potential In Chemical Defenses For Aposematic and Mimetic Systemsmentioning
confidence: 99%